2018
DOI: 10.17233/sosyoekonomi.2018.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Demokrasi, Ekonomik Özgürlükler ve Ekonomik Büyüme: Kurumların Rolü Üzerine Bir Araştırma

Abstract: The main purpose of this paper is to investigate the impact of the institutional quality on economic growth in high, medium and low-income countries in the period of 1995-2013. In this study, institutional quality is represented as a component of democracy and economic freedoms. The institutional quality index for each country is calculated by the principal component analysis (PCA) method using democracy and economic freedoms indicators. Then, the relationship between the institutional quality index and econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 53 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…On the one hand, a destination’s strong institutions and quality of governance point to a high level of security for that country. In which case, people feel more secure in the country (Tang, 2018), where incivilities can be more effectively resolved through legal mechanisms (Koçak and Uzay, 2018). Hence, the security of destinations may underlie international tourist arrivals (Ghaderi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, a destination’s strong institutions and quality of governance point to a high level of security for that country. In which case, people feel more secure in the country (Tang, 2018), where incivilities can be more effectively resolved through legal mechanisms (Koçak and Uzay, 2018). Hence, the security of destinations may underlie international tourist arrivals (Ghaderi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of underdeveloped countries, no relationship was found between the variables in the long run. Koçak (2016) investigated the relationship between democracy, economic freedom and economic growth using panel data method (panel unit root, panel cointegration, panel causality) using the 1995-2013 data of 39 high, high-middle, low-middle and low-income countries. In addition to a long-run equilibrium relationship between institutions and economic growth, it was found that the qualities of institutions have a positive effect on economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%